Heterogeneity and optimization of ecological security pattern on a mountain town: A case of Tianzhu County in the Hexi Corridor, China - Chen, Zhijie; Chen, Hong; Yang, Minan; Wang, Xi; Jiang, Yuefeng; Zhang, Wei (Frontiers in Environmental Science, 2023)
As a primary concern in the ecosystem, understanding the impact of spatial heterogeneity of ecological networks on development of the environmental sustainability has overarching significance. The Tibetan Plateau’s edge is a vital contribution to the study of the plateau’s ecological network. However, there are few studies and explorations on the county-level ecological network in the arid region. This paper aimed to evaluate ecological network spatial patterns in Tianzhu County and established an ecological security evaluation index system. The study used the Minimum Cumulative Resistance (MCR) model and built an ecological resistance surface model from the Exploratory Spatial Data Analysis (ESDA) method. Then, by identifying ecological corridors and ecological nodes from the gravity model, we analyze the ecological security pattern and propose specific plans for optimizing the situation. The results show that: (1) county ecological security overall has been lower and its values show spatial heterogeneity in each direction; (2) the Z-Score of the ecological security evaluation index is 70.1893, which shows ecological vulnerability in the arid region has significant spatial autocorrelation; (3) the study identified 156 ecological corridors and 112 ecological nodes, which formed an ecological spatial pattern of “one belt and three zones”. Our analytical framework offers a valuable tool for constructing ecological security patterns in Tianzhu County and selecting “sources” at the regional scale, which can be applied to landscapes and geographical contexts for sustainable development in arid regions.